Respiratory health in athletes: facing the COVID-19 challenge - Hull, J. H.; Loosemore, M.; Schwellnus, M. (The Lancet Respiratory Medicine, 2020)
There are unique cohorts of individuals facing specific challenges during the current global coronavirus disease 2019 (COVID-19) crisis. When faced with a rapidly evolving pandemic associated with high morbidity and mortality in older people (>60 years), the respiratory health of a (predominantly) young and very physically fit population might, on the face of it, seem trivial or almost irrelevant. Yet, for athletes, para-athletes, and clinicians concerned with their health, it is important that targeted guidance is available to ensure the wellbeing of this population is considered.